EU Taxonomy Framework in Corporate Reporting - Špilárová, Nina; Houska, Daniel; Tomčiak, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The Sustainable Finance Framework was introduced as a part of the EU´s initiative to influence how companies approach environmental challenges. The EU Taxonomy, a classification system establishing criteria to determine which economic activities qualify as environmentally sustainable, is an integral part of this framework. This thesis explores the background of the EU Taxonomy and integral components of this framework, together with the requirements needed to align with its criteria. Additionally, through semi-structured interviews with professionals, this thesis offers valuable insights from stakeholders interacting with the framework. By assessing the level of understanding of the EU Taxonomy among stakeholders, challenges posed in the early stages of adoption, and the future outlook on expected benefits, the thesis explores corporate practices and perceptions in the Slovak market.
Vedoucí práce: Daniel Houska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses